(untitled) - Ritter, Lawrence S. (New York, 1974)
Book incorporates current research and data while taking stock of sweeping changes in the international financial landscape produced by financial innovation, deregulation, and geopolitical considerations
Keywords: Stock exchanges,Thị trường chứng khoán,Banks and banking,Tiền tệ,Ngân hàng và nghiệp vụ ngân hàng,Money